Differential Regulation of Inflammation and Immunity in Mild and Severe Experimental Asthma - Seil Sagar; Kim A. T. Verheijden; Niki A. Georgiou; Johan Garssen; Aletta D. Kraneveld; Arjan P. Vos; Gert Folkerts (Hindawi Limited, 2013)
This study aimed at exploring innate and adaptive immunity in allergic asthma by investigation of mRNA expression of pattern recognition receptors, T-cell-specific cytokines, and transcription factors. Mouse models for mild and severe asthma, with similar pathological characteristics observed in humans, were used to study the involved inflammatory markers as a first step in the development of phenotype-directed treatment approaches. In the mild model, mice were sensitized to ovalbumin-Imject Alum and challenged with ovalbumin. In the severe model, mice were sensitized to trinitrophenyl-conjugated ovalbumin and challenged with trinitrophenyl-ovalbumin/IgE immune complex. Pulmonary airway inflammation and mRNA expression of Toll-like receptors (TLRs), NOD-like receptors (NLRs), T cell cytokines, and transcription factors in lung tissue were examined. Different mRNA expression profiles of TLRs, NLRs, T cell cytokines, and transcription factors were observed. In the mild model, Il10 showed the largest increase in expression, whereas in the severe model, it was Infγ with the largest increase. Expression of Tbet was also significantly increased in the severe model. Inflammation and immunity are differentially regulated in mild and severe experimental asthma. This preclinical data may help in directing clinical research towards a better understanding and therapy in mild and severe asthmatic patients.